Recombinant Avian Infectious Bronchitis Virus Expressing a Heterologous Spike Gene Demonstrates that the Spike Protein Is a Determinant of Cell Tropism - Casais, Rosa (American Society for Microbiology, 2003)
A recombinant infectious bronchitis virus (IBV), BeauR-M41(S), was generated using our reverse genetics system (R. Casais, V. Thiel, S. G. Siddell, D. Cavanagh, and P. Britton, J. Virol. 75:12359-12369, 2001), in which the ectodomain region of the spike gene from IBV M41-CK replaced the corresponding region of the IBV Beaudette genome. BeauR-M41(S) acquired the same cell tropism phenotype as IBV M41-CK in four different cell types, demonstrating that the IBV spike glycoprotein is a determinant of cell tropism.